2020
DOI: 10.1111/ppl.13087
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies and QTL mapping uncover the genetic architecture of ear tip‐barrenness in maize

Abstract: Ear tip-barrenness (ETB) phenotype threatens crop yield, because it reduces the kernel number per ear. The genetic basis of ETB in maize remains largely unknown. Herein, a genome-wide association study (GWAS) and quantitative trait loci (QTL) mapping were jointly applied to identify the significant genetic loci interrelated with ETB. Six significant SNPs were detected at a stringent P-value threshold (1.95 × 10 −6). Additionally, four environment-stable SNPs were co-detected across a single environment and bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 62 publications
0
4
1
Order By: Relevance
“…Moreover, the association panel was demonstrated to have remarkable phenotypic variations in germination traits under low temperature with the higher coefficients of variations (CVs) (0.77, 0.65, 0.45, 0.37, and 0.42 for FG, TG, RL, SL and RRS, respectively) ( Table 1 ). The observed CVs in this study were generally higher than those of the other traits among this panel in the previous studies ( Li et al, 2020 ; Liu et al, 2020 ; Ma et al, 2018 ). Estimations of broad heritability using SAS v 9.3 indicated that the H B 2 of these investigated traits ranged from 86.96%-96.56% ( Table 1 ), suggesting that these chilling-germination traits were mainly genetically controlled.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, the association panel was demonstrated to have remarkable phenotypic variations in germination traits under low temperature with the higher coefficients of variations (CVs) (0.77, 0.65, 0.45, 0.37, and 0.42 for FG, TG, RL, SL and RRS, respectively) ( Table 1 ). The observed CVs in this study were generally higher than those of the other traits among this panel in the previous studies ( Li et al, 2020 ; Liu et al, 2020 ; Ma et al, 2018 ). Estimations of broad heritability using SAS v 9.3 indicated that the H B 2 of these investigated traits ranged from 86.96%-96.56% ( Table 1 ), suggesting that these chilling-germination traits were mainly genetically controlled.…”
Section: Discussioncontrasting
confidence: 58%
“…We identified QTL that regulate both EW and EKW on chromosomes 1 and 5, and Ma et al (2019) detected similar QTL in a BC 3 F 2 population constructed from Chang 7–2 and Zheng Duqing. Zhao et al (2021) and Li et al (2020) also detected a QTL controlling BTL on chromosome 1. Liu et al (2015) used three F 2:3 populations for QTL mapping and detected loci on the same segment of chromosome 4 as qERN4‐1 in the present study, suggesting that this region contains highly reliable loci that control ear‐related traits.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 21 SNPs identified, SNP_29277326, within a MYB recognition site in the CsPPR promoter, might be the most significant. The expression levels could be affected by the genetic loci variation in promoter ( Yu et al., 2019 ; Li et al., 2020 ; Zhang et al., 2020 ). qRT-PCR and contrasting haplotypes further identified its expression level by the effect of the promoter.…”
Section: Discussionmentioning
confidence: 99%